Computational discovery of plant-derived flavonoids as potential amyloid-β fibril disaggregating agents for alzheimer’s disease - Uthirapathi Logeswari Rakesh; Golla Anil Kumar; Theivendren Panneerselvam; Parasuraman Pavadai; Suganthan Veerachamy; Ponnusamy Palanisamy; SunilKumar Bandral; Selvaraj Kunjiappan (Brain Disorders)
The neurological hallmark of Alzheimer's disease (AD) is a pathogenic deposition of amyloid-β peptide in the brain. Amyloid-β aggregation is neurotoxic and ultimately results in dysfunction of the nervous system. The present study aims to find potential amyloid-β fibrils disaggregating molecules from plant sources through molecular modeling techniques, which seems to be a promising and attractive therapeutic approach. Here, 500 flavonoids from various plants were considered, initially undergoing ADME studies to screen molecules that could cross the blood-brain barrier. Later, potential Amyloid-β-disaggregating molecules were predicted by molecular docking and molecular dynamics studies. Five molecules, prenylmethoxy flavonol (-7.3 kcal × mol-1), isopentenyl flavonol (-7.3 kcal × mol-1), 7,3′-Dihydroxyflavone (-7.2 kcal × mol-1), 7-Hydroxy-5-methyl-4′-methoxyflavone (-7.2 kcal × mol-1), 8‑hydroxy-7-methoxyflavone (-7 kcal × mol-1) exhibited top binding score against Alzheimer's Aβ (1–42) fibrils, and these are very close to the standard drug (Donepezil) (-7.90 kcal × mol-1). Further, the MD simulation studies confirmed the stability of the five selected ligands-Amyloid-β oligomer protein complex. Based on these findings, the selected five compounds might be used as potential Amyloid-β fibril disaggregating agents, and in vitro and in vivo studies are necessary to confirm the promising therapeutic capability.